"Are people thinking I'm a vector…because I'm fat?": Cisgender experiences of body, eating, and identity during COVID-19. (March 2022) - Brownstone, Lisa M.; Greene, Amanda K.; Kelly, Devin A.; Maloul, Elana K.; Norling, Hannah N.; Rockholm, Reagan H.; Izaguirre, Cristine M.
Highlights: Participants described changed experience of body and eating prompted by COVID-19. Many described increased body dissatisfaction and fixation on intake and movement. Participants linked resource concerns like food scarcity to problematic eating. Participants connected changed visibility to body/eating relief and distress. Those with marginalized identities reported body vulnerability linked to COVID-19. Abstract: While a range of studies have shown the negative impact of COVID-19 on disordered eating and body image, few have engaged with how identity and social context interact with these domains. The current study used inductive codebook thematic analysis to understand experiences of body and eating during the pandemic among a diverse (sub)clinical sample of individuals with self-reported disordered eating. We interviewed 31 cisgender participants (18/31 Black Indigenous People of Color (BIPOC), 24/31 women) with a history of disordered eating (diagnosed and undiagnosed). Five themes were identified: Body Surveillance and Dissatisfaction, Movement and Intake Fixation, Food Scarcity and Resource Concerns, Changes in Visibility of Body and Eating, and Bodies Are Vulnerable. We examined the extent to which themes pertained to certain identities over others. Notably, BIPOC, large-bodied, queer participants more commonly spoke to body vulnerability than White, small/medium-bodied, straight participants. BIPOC and large-bodied participants also particularly spoke to feeling relief from discrimination as social distancing and mask wearing reduced their public visibility. Participants related these themes to changed body and eating experiences that spanned distress and resilience. Our analysis offers insight into multifaceted and contextual impacts of COVID-19 on experiences of body, eating, and identity.